Kerjasama BNN (Badan Narkotika Nasional) Indonesia dan NNCC (National Narcotics Control Commissions) Tiongkok dalam Menanggulangi Perdagangan Narkotika Asal Tiongkok di Indonesia Tahun 2012 - 2018 - Perwira, Aldebaran Yudha; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Drugs trafficking is one of the transnational crimes which is increasing every year in Indonesia. Indonesia is one of the destination countries for international drug suppliers because of its promising market for drug traffickers. One of the biggest drugs suppliers in Indonesia is China. Therefore, both the Government of Indonesia and the Chinese Government agreed to create a cooperation that is contained in the form of a Memorandum of Understanding. This study analyzed how the compliance of Indonesia and China in running the Memorandum of Understanding that has been formed in dealing with cases of drugs smuggling through the sea. The author will use the theory of compliance from Ronald B. Mitchell and seen from the point of view of Indonesia because Indonesia is a destination country of drugs smugglers from China. A compliance is closely related to the effectiveness of a form of cooperation. The compliance here will be measured based on the implementation of the MoU.